Comparative law and economics - Eisenberg, Theodore; Ramello, Giovanni B. (Research handbooks in comparative law, 2016)
The Past, Present and Future of Comparative Law and Economics / Giovanni B. Ramello -- Markets, Contracts, and Firms: A Unified Model of Organizational Choice / Thomas J. Miceli -- Law, Social Norms, and Standards: Their Nexus with Government and their Impact on the Economic Performance of Nation States / Nicholas Mercuro -- The Market for Legal Innovation: Law and Economics in Europe and the United States / Nuno Garoupa and Thomas S. Ulen -- Principles, Tolerance and Institutional Torpor / Enrico Colombatto -- Structure and Style in Comparative Property Law / Yun-chien Chang and Henry E. Smith -- A Comparative View of Local Tax and Expenditure Limitations and their Consequences / Federico Revelli -- Iron Fist in a Velvet Glove? Judicial Behavior in Mixed Courts / Valerie P. Hans and Anne Jolivet -- Global Competition Law Convergence: Potential Roles for Economics / David J. Gerber -- The Comparative Law and Economics of Energy Markets / Giuseppe Bellantuono -- A Comparative Law and Economics Analysis of Damages for Patent Infringement / Thomas F. Cotter -- The Comparative Economics of International Intellectual Property Agreements / Peter K. Yu -- Copyright and Tort as Mirror Models: On Not Mistaking for the Right Hand What the Left Hand is Doing / Wendy J. Gordon -- The Eurozone Crisis, the Defective Policy Response and the Need for Institutional Innovation / Enrico Marelli and Marcello Signorelli -- The Effect of Stakes on Settlement: An Empirical Lesson from Taiwan / Kuo-Chang Huang -- Comparative Judicial Efficiency: Examining Case Disposition in Five Countries' Courts of Last Resort / Anthony Kreis, John Szmer and Robert K. Christensen -- Copyright Law and the Supply of Creative Work: Evidence from the Movies / Ivan Paak Liang Png and Qiu-hong Wang -- International Environmental Agreement Effectiveness: A Review of Empirical Studies / Kendall A. Houghton and Helen T. Naughton -- The American and the European Market of Human Experimentation, A Comparative Study on Regulation and Competitiveness / Antonella Foddis and Roberto Ippoliti